Dietary substitution of SFA with MUFA within high-fat diets attenuates hyperinsulinaemia and pancreatic islet dysfunction. Issue 3 (3rd March 2020) - Ralston, Jessica C.; Nguyen-Tu, Marie-Sophie; Lyons, Claire L.; Cooke, Aoife A.; Murphy, Aoife M.; Falvey, Aidan; Finucane, Orla M.; McGillicuddy, Fiona C.; Rutter, Guy A.; Roche, Helen M.
Abstract: Preliminary evidence has suggested that high-fat diets (HFD) enriched with SFA, but not MUFA, promote hyperinsulinaemia and pancreatic hypertrophy with insulin resistance. The objective of this study was to determine whether the substitution of dietary MUFA within a HFD could attenuate the progression of pancreatic islet dysfunction seen with prolonged SFA-HFD. For 32 weeks, C57BL/6J mice were fed either: (1) low-fat diet, (2) SFA-HFD or (3) SFA-HFD for 16 weeks, then switched to MUFA-HFD for 16 weeks (SFA-to-MUFA-HFD). Fasting insulin was assessed throughout the study; islets were isolated following the intervention. Substituting SFA with MUFA-HFD prevented the progression of hyperinsulinaemia observed in SFA-HFD mice ( P < 0·001). Glucose-stimulated insulin secretion from isolated islets was reduced by SFA-HFD, yet not fully affected by SFA-to-MUFA-HFD. Markers of β -cell identity ( Ins2, Nkx6.1, Ngn3, Rfx6, Pdx1 and Pax6 ) were reduced, and islet inflammation was increased (IL-1 β, 3·0-fold, P = 0·007; CD68, 2·9-fold, P = 0·001; Il-6, 1·1-fold, P = 0·437) in SFA-HFD – effects not seen with SFA-to-MUFA-HFD. Switching to MUFA-HFD can partly attenuate the progression of SFA-HFD-induced hyperinsulinaemia, pancreatic inflammation and impairments in β -cell function. While further work is required from a mechanistic perspective, dietary fat may mediate its effect in an IL-1 β –AMP-activated protein kinase α 1-dependent fashion. Future work should assess the potential translation of the modulation of metabolic inflammation in man.